2016
DOI: 10.1089/jwh.2015.5735
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of Primary Care Physicians to Evidence-Based Recommendations to Reduce Ovarian Cancer Mortality

Abstract: Ovarian cancer is the deadliest gynecologic cancer. Receipt of treatment from a gynecologic oncologist is an evidence-based recommendation to reduce mortality from the disease. We examined knowledge and application of this evidence-based recommendation in primary care physicians as part of CDC gynecologic cancer awareness campaign efforts and discussed results in the context of CDC National Comprehensive Cancer Control Program (NCCCP). We analyzed primary care physician responses to questions about how often t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
9
1
Order By: Relevance
“…The CDC's NCCCP operates in all 50 states, the District of Columbia, 7 tribal governments and organizations, and 7 territories and US‐associated Pacific Island jurisdictions to support the development and implementation of evidence‐based initiatives to prevent and control cancer . Recent studies have documented prior ovarian cancer activities of the NCCCP; nearly one‐half of programs are undertaking activities related to ovarian cancer, which largely center on education, primary prevention, and implementation of interventions to improve ovarian cancer survivors’ well being . Primary prevention activities include promoting smoking cessation and smoke‐free environments, because smoking is a risk factor for some types of ovarian cancer, as well as the promotion of breastfeeding among women who have the opportunity, which several studies have suggested reduces risk for epithelial ovarian cancer .…”
Section: Discussionmentioning
confidence: 99%
“…The CDC's NCCCP operates in all 50 states, the District of Columbia, 7 tribal governments and organizations, and 7 territories and US‐associated Pacific Island jurisdictions to support the development and implementation of evidence‐based initiatives to prevent and control cancer . Recent studies have documented prior ovarian cancer activities of the NCCCP; nearly one‐half of programs are undertaking activities related to ovarian cancer, which largely center on education, primary prevention, and implementation of interventions to improve ovarian cancer survivors’ well being . Primary prevention activities include promoting smoking cessation and smoke‐free environments, because smoking is a risk factor for some types of ovarian cancer, as well as the promotion of breastfeeding among women who have the opportunity, which several studies have suggested reduces risk for epithelial ovarian cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Behavior. 11,[24][25][26][27][28][29][30] While the Theory of Reasoned Action focuses on understanding attitudes, intentions, and beliefs as determinants of behaviors, the Theory of Planned Behavior accounts for factors beyond the interviewee's control that limit or facilitate one's behaviors and choices.…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5][6][7][8] Current National Comprehensive Cancer Network (NCCN) clinical guidelines and other national organizations recommend that all women with stage IB-IV ovarian cancer receive surgical care from a gynecologic oncologist. 3,[9][10][11][12][13] Despite the evidence of improved outcomes and NCCN recommendations, as many as 30% of women with ovarian cancer in the United States and nearly 15% of women in Iowa are not receiving surgical care from a gynecologic oncologist. 11,[14][15][16][17][18][19][20] Researchers have hypothesized this discrepancy between recommended and received care is due to the incidental diagnosis, discovery of cancer during non-cancer surgery and disagreement about standards of care.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations